ຄວາມຮັບຜິດຊອບຕໍ່ສັງຄົມ ຂອງອົງກອນ (CSR) ໃນວຽກງານ ການພັດທະນາເຂື່ອນໄຟຟ້າໃນແມ່ນໍ້າຂອງ - West, Niki (CGIAR Challenge Program on Water and Food, 2013)
Reviews current literature on definitions of CSR, main international frameworks, criticisms, CSR in Asia, CSR in hydropower, and drivers and trends in CSR.